2015
DOI: 10.3892/ol.2015.3936
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal laparoscopic management of a solitary extramedullary plasmacytoma associated with human immunodeficiency virus infection: A case report

Abstract: Abstract. Extramedullary plasmacytoma (EMP) is a rare malignant tumor that is characterized by a malignant plasma cell neoplasm. Such neoplasms in human immunodeficiency virus (HIV)-infected patients are extremely rare. To the best of our knowledge, the present study describes the first case of a solitary adrenal EMP in a patient with HIV. A 35-year-old male who had been diagnosed with HIV 3 months previously presented with a 2-week history of intermittent right flank pain. Abdominal computed tomography reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Intra-abdominal extramedullary plasmacytoma usually has an indolent life course and manifests by mass effect on surrounding viscera. This can present as abdominal pain, 2,3 intestinal obstruction 4,5 or hydronephrosis. 6 Intraluminal disease can also present with symptoms mimicking other common gastrointestinal malignancies, such as microcytic anaemia, melaena, 7 haematochezia, 8 intussusception, 9 localised perforation 10 or tenesmus.…”
Section: Narrative Review Presentationmentioning
confidence: 99%
“…Intra-abdominal extramedullary plasmacytoma usually has an indolent life course and manifests by mass effect on surrounding viscera. This can present as abdominal pain, 2,3 intestinal obstruction 4,5 or hydronephrosis. 6 Intraluminal disease can also present with symptoms mimicking other common gastrointestinal malignancies, such as microcytic anaemia, melaena, 7 haematochezia, 8 intussusception, 9 localised perforation 10 or tenesmus.…”
Section: Narrative Review Presentationmentioning
confidence: 99%
“…Such neoplasms in this group of patients are extremely rare [9]. In addition, this tumor shows a different clinical behavior among HIV patients: occurrence in a younger age group, with a shorter latency period, with often extramedullary involvement and in a more aggressive clinical course, with a poor prognosis due to the poor immunity of the patient [9, 1114]. Indeed, the mean of age of EMP is 60 years in noninfected patients [2], but in HIV-positive patients the mean age is 33 years [15].…”
Section: Discussionmentioning
confidence: 99%
“…EMP has been treated with surgical excision, radiotherapy, chemotherapy, or combined surgery and radiotherapy [9]. EMP is a highly radiosensitive lesion; however, no firmly dose-response relationship has been established due to small patient series and low local failure rates [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ahmed et al [13] reported bilateral regression of the adrenal tumors with calcification and fibrosis after two consecutive autologous hematopoietic stem cell transplantation. Cao et al [14] reported the first case of extramedullary plasmacytoma involving the adrenal gland in an HIV-positive 35-year-old male patient. Of the six cases that have reported follow-up data on adrenal EMP, the follow-up ranging was from 12 to 72 months, with no recurrences.…”
Section: Case Reports In Urologymentioning
confidence: 99%